2018
DOI: 10.1073/pnas.1711017115
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear export of ubiquitinated proteins via the UBIN-POST system

Abstract: SignificanceIt is commonly observed that proteasome impairment results in accumulation of ubiquitinated proteins in the cytosol. Even proteins originally located in the nucleus show similar cytosolic accumulation, suggesting that unidentified machinery proactively transports them to the cytosol. Here, we report that a protein complex, UBIN–polyubiquitinated substrate transporter, harboring ubiquitin binding domain and nuclear export signal specifically mediates this process. In addition, their worm homologues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 54 publications
2
32
0
1
Order By: Relevance
“…The APEX2 results suggest that UBQLNs may not only deliver proteins to the proteasome to be degraded but also promote proteasome-independent signaling roles of ubiquitin. For more information regarding this experiment, see Supplemental Discussion and Table S4 ( 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ).…”
Section: Resultsmentioning
confidence: 99%
“…The APEX2 results suggest that UBQLNs may not only deliver proteins to the proteasome to be degraded but also promote proteasome-independent signaling roles of ubiquitin. For more information regarding this experiment, see Supplemental Discussion and Table S4 ( 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ).…”
Section: Resultsmentioning
confidence: 99%
“…The search for novel cargos is still on-going, and continues to provide further insight into the physiological relevance of XPO1. For example, it has been recently found that the NES-containing protein POST and the ubiquitin-binding protein UBIN form a complex that mediates XPO1-dependent nuclear export of polyubiquitinated proteins [35] , a process that seems to be exacerbated in cancer cells treated with the proteasome inhibitor bortezomib [36] . These findings reveal a novel role for XPO1 in nuclear protein homeostasis that might also have important implications for cancer therapy.…”
Section: Xpo1-mediated Protein Nuclear Export: Cargos Mechanisms Andmentioning
confidence: 99%
“…However, proteasomal inhibition or the inability of the proteasome to recognize the substrate would stabilize the polyubiquitinated proteins, thus their transport across the NE could be envisaged. In line with this possibility, the experiments with mammalian cell lines treated with the proteasome inhibitors showed active transport of polyubiquitinated proteins from the nucleus to the cytoplasm by a nuclear export pathway [ 111 ]. In response to proteasome inhibition, K48-linked polyubiquitinated proteins were exported to the cytosol in a CRM1 (exportin-1 [ 112 ]) dependent manner, via interaction of polyubiquitinated proteins with a protein complex consisting of the ubiquitin-binding protein UBIN (UBQLN4, [ 113 ]) and a NES-containing protein termed polyubiquitinated substrate transporter (POST) [ 111 ].…”
Section: Discussionmentioning
confidence: 99%